Pengaruh Edukasi Audio Visual Berbasis Android terhadap Pengetahuan Pemilahan Sampah pada Anak Usia Sekolah di SDN Sendangrejo II Lamongan - Rahmat Agung Firmansyah; Dadang Kusbiantoro; Sylvi Harmiardillah; Dhiajeng Widya Ningrum; Fajar Suci Aristanto (Inovasi Kesehatan Global, 2024)
Garbage will cause health problems if not managed properly. The increase in waste along with the rate of population growth and ignorance of sorting waste according to its type is a problem that must be resolved. As is the case with students at SDN Sendangrejo II Lamongan. This study aims to determine the effect of audio-visual education on knowledge of sorting waste at SDN Sendangrejo II Lamongan. The study used a pre-experimental one group post test design. The population of all students in grades 1-6 at SDN Sendangrejo II Lamongan was 44 respondents using SPSS 26.0 using a total sampling technique, the research instrument used a questionnaire, then the results were analyzed using the Wicoxon test with a significance level of p <0.05. The results of the study showed that before being given audio-visual education about sorting waste, it was found that almost all students (81.8%) had a low level of knowledge and after being given audio-visual education, it was found that most students (72.7%) had a good level of knowledge. Video is one of the educational media that can increase one's knowledge because the material presented can be received through the senses of sight and hearing. It is recommended that educators use this audio- visual technique in providing education or learning activities.